Determination Modal parameters a Turning machining system - Юрій Петраков; Олександр Охріменко; О. Пасічник; А. Петришин (Mechanics and Advanced Technologies, 2025)
Among various machining processes, turning accounts for the largest volume of chip removal worldwide, so much attention is paid to predicting stability and preventing chatter, with a special emphasis on machining systems. The use of CNC machines expands the possibilities for controlling the cutting process in accordance with the Stability Lobes Diagram (SLD), which allows not only to ensure the required quality and the reduce of vibrations, but also to select the cutting mode that ensures maximum productivity. Designing a SLD involves building a mathematical model of the machining system, which is associated with determining its dynamic characteristics. A dynamic model of the machining system of a lathe has been developed as a composition of the main units using the receptance coupling method, which made it possible to calculate the rigidity of the entire system, reduced to the tip of the cutter, as a function of the longitudinal coordinate when machining a workpiece installed in a chuck and in a chuck and rear center. The cutting process model represents the components of the cutting forces acting along the coordinate axes, which allows it to be integrated into the structure of the machining system. A method for experimental modal analysis of the machining system of a lathe using a hammer, accelerometer and a storage two-channel oscilloscope has been developed. Software for determining the frequency response function using a digital file of the experimental impulse response function has been created.